(untitled) (American Journal of Youth and Women Empowerment, 2024)
Recent economic trend has recorded increasing adoption of digital technology in the world of finance, yet the challenge of financial literacy and poor access to digital financial services by women entrepreneurs in Nigeria continues to plague the entrepreneurial endeavors of women, triggering a great concern to policy makers. Access to digital finance represents not just a formidable opportunity but a crucial imperative in empowering women entrepreneurs, therefore this research investigated the transformative potential of digital financial services in improving the performance and empowerment of women entrepreneurs in Abuja municipal area council (AMAC). The paper employed a descriptive research design based on primary data, using survey questionnaires, targeted at three hundred and eighty-four (384) respondents, and administered to both registered and unregistered women entrepreneurs. Responses to questionnaires were collated and analyzed using the ordinal logistic regression method to reveal a significant and beneficial correlation between the variables. The paper confirmed that access to digital financial services (DFS) has a positive impact on the performance and empowerment of female entrepreneurs as it provided crucial financial tools, improved decision making and encouraged financial independence. Based on the findings, the paper therefore recommended the implementation of specialized financial solutions offering credit and savings products, robust digital infrastructure development by the government, and advocacy for gender-responsive policies to further drive practical changes for women entrepreneurs. The paper concluded by advocating a joint action to promote women’s empowerment and economic growth by leveraging the transformative power of digital financial services.